Curso de Matemática Licenciatura/UFSM no período 2014 – 2019: uma análise a partir da perspectiva do desenvolvimento profissional no âmbito do PIBID - Viero, Vartieli Lopes (2021)
The objective of this dissertation is to identify aspects of professional development favored in the academic trajectory of licentiates in Mathematics (2014-2019), participants in Pibid Mathematics/UFSM, considering learning and professional knowledge. Therefore, the work is based on the theoretical assumptions of professional development, taking into account that this is a process by which teachers review, renew and improve their teaching practice. Therefore, this initiative includes reflections and changes that lead to a transformation of the teacher. Through a qualitative approach, guided by the content analysis technique, this work is structured in a multipaper format. Thus, each manuscript has a specific objective, namely: to characterize the trajectory of licentiates in the Mathematics Course, participants in Pibid Mathematics/UFSM, in the period 2014-2019; investigate articulations between theory and practice, based on the understanding of licentiates participating in Pibid Mathematics/UFSM and the Pedagogical Project of the Mathematics Course; and to analyze impressions revealed by Initiation Scholarship Students about experiences resulting from their participation in Pibid Mathematics/UFSM, in the period from 2014 to 2018. In addition, the three manuscripts consider the examination carried out on the questions of a questionnaire answered by 18 participants. Among the results, it appears that the course had 572 admissions linked to PPC-2013, of which 78 (13.64%) graduated; 160 (27.97%) remained as regular students; and 334 (58.39%) dropped out. With regard to participation in teaching, research and extension projects registered with GAP/UFSM, the percentage concerning Pibid had the largest number of graduates. According to the analysis of PPC-2013, the favored aspects that relate theory and practice refer to Mathematics: Treatment of School Mathematics; Teaching of Mathematics: Didactic-pedagogical reflections; Empirical research in the school environment; and Course Conclusion Paper. In relation to Pibid Mathematics/UFSM, in addition to favoring the permanence of students and the conclusion of the course, such aspects are associated with the dimensions previously identified. That is, Mathematics and the Teaching of Mathematics, with: Teaching processes in the classroom; Mathematical learning of students; and Insertion in the school environment, in addition to Breaks in Professional Culture, being: Professional autonomy; Reflection on practice; Research on practice; Researcher professor; Social representations; and Collaborative work based on mutual support.